Comparative study on eating habits and health of single-person and multi-person households - Haerang Lee; Seon-Jip Kim; Minji Kang (PLoS ONE, 2025)
This study investigates the differences in health, dietary habits, and quality of life between single-person and multi-person households, with a specific focus on demographic subgroups such as gender and age. Data were drawn from the 2013–2021 Korean National Health and Nutrition Examination Survey, encompassing 40,839 participants aged 19 and older, and were analyzed using multivariate regression models. The results revealed significant disparities between the two types of households. Single-person male households exhibited poorer dietary quality and higher metabolic risk indicators, such as elevated waist circumference, low-density lipoprotein cholesterol, and blood pressure, compared to their multi-person counterparts. In contrast, single-person female households demonstrated slightly better metabolic profiles, including lower body mass index, triglycerides, and fasting glucose, relative to multi-person households. Quality of life, assessed using the EuroQol-5 Dimension, was significantly lower in single-person households, with women reporting higher rates of anxiety, depression, and mobility issues. Subgroup analyses identified pronounced vulnerabilities among single-person males aged 40–59 and single-person females aged 60 and older. These findings highlight the need for tailored public health policies and market strategies to address the distinct needs of diverse single-person household subgroups. Further research should prioritize well-designed studies exploring populations with unique characteristics, such as single-person households, to better understand their specific challenges and requirements compared to multi-person households.